A pulse‐dose topical 1% 5‐fluorouracil treatment regimen in a young dog with corneal squamous cell carcinoma. (1st October 2014) - Overton, Taryn L.; Allbaugh, Rachel A.; Whitley, David; Ben‐Shlomo, Gil; Griggs, Angel; Tofflemire, Kyle L.; Whitley, Elizabeth M.
Abstract Purpose To describe the use of a pulse‐dose topical 5‐fluorouracil (5‐FU) treatment regimen in a Pug dog with corneal squamous cell carcinoma (SCC). Methods A 1‐year‐old, spayed female Pug was evaluated for a corneal perforation of the right eye, which was surgically stabilized with a conjunctival pedicle graft. At the time of medial canthoplasty 7 weeks later, two areas of gray–white discoloration had developed medial and lateral to the graft. Biopsy samples were obtained via superficial keratectomy while under general anesthesia. Results Definitive diagnosis of corneal SCC was made through histopathological examination of the surgical biopsies. Thoracic radiography and submandibular lymph node cytology revealed no evidence of metastatic neoplasia. Following healing of the corneal biopsy sites, topical 1% 5‐FU ointment was applied four times daily for four consecutive days once a month, for six treatment cycles. Twenty‐three months after diagnosis, the patient remains visual and comfortable with no evidence of SCC recurrence. Long‐term therapy with once daily topical 1% cyclosporine solution was used to manage corneal pigmentation bilaterally. Conclusions The pulse‐therapy 1% 5‐FU protocol was a successful, convenient, and cost‐effective adjunctive treatment with few adverse effects.